Answer:
v = at + u
![x = ut+(1)/(2)at^(2)+x_(0)](https://img.qammunity.org/2020/formulas/physics/college/ssoguftmy75iyjd4ncxqd6sk04o0g7etri.png)
Step-by-step explanation:
acceleration, a = constant
As we know that acceleration is the rate of change of velocity
![a=(dv)/(dt)](https://img.qammunity.org/2020/formulas/engineering/college/milvn3hs3agmnqjxewhtrz14i1td3s69q7.png)
![dv=adt](https://img.qammunity.org/2020/formulas/physics/college/hkqy4ot7sv8t3suhqasvka4nzk3gtg7lne.png)
integrate on both sides
![\int dv=\int adt](https://img.qammunity.org/2020/formulas/physics/college/hwkyt0vmbcee5pcfhatn1ail9c5kzwmxm3.png)
v = at + u
Where, u is the integrating constant and here it is equal to the initial velocity
Now we know that the rate of change of displacement is called velocity
![v = (dx)/(dt)](https://img.qammunity.org/2020/formulas/physics/college/6gdgnjntwyl21gjjnk2kyzh2em161fhnn6.png)
![dx=vdt=(u+at) dt](https://img.qammunity.org/2020/formulas/physics/college/6s4rnrbn9vd7ui9ct534jil1vz4r1q79bw.png)
Integrate on both sides
![\int dx=\int (u+at) dt](https://img.qammunity.org/2020/formulas/physics/college/beu6fjvqtywy9nb6wb88nu40v9q9c063pl.png)
![x = ut+(1)/(2)at^(2)+x_(0)](https://img.qammunity.org/2020/formulas/physics/college/ssoguftmy75iyjd4ncxqd6sk04o0g7etri.png)
where, xo is the integrating constant which is initial position of the particle.